The effect of Corporate Social Responsibility (CSR) and Word Of Mouth (WOM) upon the image of the company (case study at Hotel Whiz Prime Bogor) - Vera Clara Simanjuntak (The Management Journal of Binaniaga, 2019)
This study aims to explain the Effect of Corporate Social Responsibility (CSR) and Word of Mouth (WOM) upon Corporate Image (Case Study of Bogor Whiz Prime Hotel). The analytical tool used in this study is Multiple Linear Regression which was first tested using validity and reliability tests. The data analysis technique used in this study is using SPSS 24.0 computer statistical software. The sampling method taken was 120 respondents. The results of this study indicate that Corporate Social Responsibility (CSR) has a significant effect on the Image of Whiz Prime Bogor Company, Word of Mouth (WOM) has a significant effect on the Image of Bogor Whiz Prime Hotels, Corporate Social Responsibility (CSR) and Word of Mouth (WOM) simultaneously has been influencing the Company Image of Bogor Whiz Prime Hotel. Keywords: Corporate Social Responsibility (CSR), Word Of Mouth (WOM), Corporate Image